Role of Entrepreneurial Behavior in Achieving Sustainable Digital Economy - Wang, Ying; Zhou, Han; Zhang, Yanan; Sun, XiaoRan (Frontiers in Public Health, 2022)
Entrepreneurship is a key indicator of not only personal growth but also economic growth by proposing a solution to worldwide problem of unemployment. The main purpose of this study is to measure the role of entrepreneurial self-efficacy and expectancy-value belief in digital economy among the students enrolled in universities of China. In this study quantitative approach was used for measuring the impact of entrepreneurial self-efficacy for achieving the entrepreneurial success along with expectancy-value belief wih the support of theories of entrepreneurial self-efficacy theory and achievement goal theory. The population frame for this study is the students of universities enrolled in degrees in China who were selected for data analysis through convenience sampling. The sample size for the study was 324. The data for the study has been analyzed using Smart-PLS software. The current study has been a contribution to the literature by measuring the role of entrepreneurial self-efficacy in entrepreneurial intentions, expectancy-value belief, and the entrepreneurial success and ultimate role in attaining the digital economy. The study has found that in this digital era, entrepreneurial success and expectancy-value belief are significantly predicted by entrepreneurial self-efficacy which in turn significantly predict the achievement of the digital economy in this progressing century. Furthermore, entrepreneurial success has been found to be an important mediator in the relationship between entrepreneurial self efficacy and digital economy for the present study. Moreover, entrepreneurial success has also significantly mediated the relationship of expectancy value belief and digital economy. This study is considerable for the universities in employing those study programs that help the motivated students in starting their businesses and such workshops should be made part of the curriculum to achieve their entrepreneurial goals and reach the expected success in entrepreneurship.